Studi Analisis Terhadap Implementasi Perda Nomor 1 Tahun 2014 Tentang Penyelenggaraan Pertanian Pangan Berkelanjutan dalam Upaya Meningkatkan Kualitas Hasil Pertanian di Kabupaten Ciamis - Lilis Nurlaela Adi Wulandari; Irma Bastaman (International Forum of Researchers and Lecturers, 2023)
This research is motivated by the results of preliminary observations that the Implementation of Sustainable Food Agriculture seems too forced, without any review of the existing situation and conditions. In Regional Regulation Number 1 of 2014 concerning the Implementation of Sustainable Food Agriculture, it is known that there is a clause on sustainable food land zoning, whereas the existence of the Regional Spatial Plan (RT RW) which is the reference is in the process of technical review related to the formation of the New Autonomous Region of Pangandaran Regency. As a result of all that, it is indicated that the quality of agricultural products is not being considered, whereas the main purpose of the regulation is to improve the quality of food crops. The method used is a qualitative descriptive research method. The population in this study was 10 people. The results of the study obtained are as follows: (1. The implementation of Regional Regulation Number 1 of 2014 concerning the Implementation of Sustainable Food Agriculture in Ciamis Regency is said to be effective if it meets the criteria for effectiveness such as the existence of policy objectives or targets, the existence of activities or activities to achieve objectives, and the existence of activity results. (2. The obstacles faced by the government in the implementation of Regional Regulation Number 1 of 2014 concerning the implementation of sustainable food agriculture are the status of land ownership owned by individuals; inventory and determination of land that may not be converted are difficult to carry out; the application of incentives and compensation is very difficult to implement; protection and empowerment of farmers; financing in the protection of food agricultural land requires a lot of money/funds. (3. The obstacles faced by the government in the implementation of Regional Regulation Number 1 of 2014 concerning the implementation of sustainable food agriculture are the status of land ownership owned by individuals; inventory and determination of land that may not be converted are difficult to carry out; the application of incentives and compensation is very difficult to implement; protection and empowerment of farmers; financing in protecting agricultural land requires a lot of money/funds. (4. Efforts made by the government in implementing Regional Regulation Number 1 of 2014 concerning the Implementation of Sustainable Food Agriculture, are Sovereignty of agricultural land by the State; Financing the implementation of sovereign food agriculture, the authority is assigned to the central level; and the authority to organize food agriculture must be returned to the central level.